Interrelationship Among Rice Grain Arsenic, Micronutrients Content and Grain Quality Attributes: An Investigation From Genotype × Environment Perspective - Moulick, Debojyoti; Ghosh, Dibakar; Skalicky, Milan; Gharde, Yogita; Mazumder, Muhammed Khairujjaman; Choudhury, Shuvasish; Biswas, Jayanta Kumar; Santra, Subhas Chandra; Brestic, Marian; Vachova, Pavla; Hossain, Akbar (Frontiers in Environmental Science, 2022)
Background. Arsenic contamination in rice agro-ecosystem, consequent spread into the food chain and it’s the adverse impact is a global concern. However, the impact of arsenic contamination on the qualitative aspect of rice has not been attempted in the post-harvest phase. Methods. We laid down this particular experiment with the aim to assess how arsenic contamination influences grain quality attributes and other elemental profiles of four popular rice varieties. The entire field study was conducted in the Lower–Indo-Gangetic Plane from genotypes and environment interaction point of view, using the additive main effects and multiplicative interaction (AMMI) model. Results. Our findings indicate that grain arsenic content can influence grain quality attributes and other elemental profiles in low to highly significant manner. Amylose content (r = 0.753) and cooking time (r=0.706) were found to be positively correlated with grain arsenic content in high yielding varieties. Noteworthy variations in micronutrient content like iron (6.63-9.23 mg Kg-1), zinc (3.15-5.54mg Kg-1) as well as soil properties are visible. Moreover, indigenous rice varieties respond differently than high yielding varieties. Besides these, a pronounced impact of gene and environment interaction can be seen. Conclusion. These outcomes will attract the attention of policymakers and researchers to develop rice varieties having desirable quality attributes appropriate for arsenic-contaminated regions of the world for sustainable rice production.